Density of Meretrix meretrix Clamps Under Ecological Pressure on Different Substrate Texture at the Kambu River of Kendari Bay, Southeast Sulawesi - Bahtiar; Muhammad Fajar Purnama (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
White clams at the mouth of the Kambu River in Kendari Bay have a preference for different substrate textures and are under ecological pressure. This study aims to determine the density of tofu shells at the mouth of the Kambu River, Kendari Bay, Southeast Sulawesi. This research was conducted at the estuary of the Wanggu River, Kendari Bay, Southeast Sulawesi from August 2021 to January 2022. White clams were taken manually using a 1x1 m squared transect. These shellfish samples were taken 6 times in repetition/station in each month of observation. Samples found in the field were counted. Taking the texture of the aquatic substrate together with the sampling of shellfish. The results showed that the maximum density of white clams at the mouth of the Kambu River, Kendari Bay, was 7.3 ind/m2. The highest density of white clams was found at stations I and II, while the lowest density was found at station III. The highest density of shellfish was found in the type of substrate which was dominated by the fine sand fraction, while the lowest density was found in the type of substrate which was dominated by the silt fraction.